C4.5 Forward Selection Based Algorithm For Class Level Classification Of Nurul Jadid Islamic Boarding School Students - Irfan, Muhammad Isomul (Politeknik Ganesha Medan, 2024)
Pesantren is an Islamic educational institution that plays a central role in the development of education in Indonesia. Although originally established for Islamic religious education (Pendidikan Agama Islam or PAI), pesantren has evolved into an educational institution that contributes to both scholarly and community service aspects. According to the regulations set by the Ministry of Religious Affairs of the Republic of Indonesia under Number 31 of 2020, pesantren is a community-based institution that upholds the teachings of Islam rahmatan lil'alamin (Islam as a blessing for all) and the noble values of the Indonesian nation. Pesantren education is efficient because it is conducted in a boarding school setting, which shapes the character of its students or 'santri.' However, the current method of determining the grade levels of santri is often inaccurate, relying solely on the average scores of entrance exams without considering essential aspects of subjects. This leads to a decrease in students' interest in learning and delays in achieving higher levels of education. By utilizing data mining techniques, such as the C4.5 algorithm based on Forward Selection, it is possible to address this issue and enhance the accuracy of placing santri into their appropriate grade levels at the Nurul Jadid Paiton Probolinggo pesantren. This improvement can make the pesantren education system more effective in managing student learning